Recent advances in alkali-doped polybenzimidazole membranes for fuel cell applications. (June 2018) - Wu, Q.X.; Pan, Z.F.; An, L.
Abstract: Polybenzimidazole (PBI), with a well-known excellent thermal stability, has been recognized as an alternative for anion exchange membrane fuel cells (AEMFC), primarily because it can serve as an ionic conductor after doping with inorganic hydroxides (typically KOH/NaOH) and thus allows fuel cells to be operated at high temperatures (currently as high as 120 °C). In addition, alkali-doped PBI membranes also offer many other favored physiochemical properties, such as high ionic conductivity. The objective of this article is to provide a review of recent research on the alkali-doped PBI membranes and their applications in fuel cells, including mechanisms of ion conduction through the alkali-doped PBI membranes, stability of the PBI membranes doped with alkali, strategies aiming at improving the ionic conductivity of the PBI membranes doped with alkali, as well as the performance of alkali-doped PBI membrane based fuel cells. Additionally, future perspectives relating to the development of alkali-doped PBI membranes and their applications in fuel cells are also highlighted. Highlights: This article reviews the past research on alkali-doped PBI membranes. Particular attention is paid to their physicochemical properties. Selected single-cell performance is summarized and discussed.